ALIGNed on adherence: subanalysis of adherence in immune‐mediated inflammatory diseases in the DACH region of the global ALIGN study. (22nd August 2018) - Kolios, A.G.A.; Hueber, A.J.; Michetti, P.; Mrowietz, U.; Mustak‐Blagusz, M.; Sator, P.‐G.; Reinshagen, M.; Wilsmann‐Theis, D.; Gomis‐Kleindienst, S.; Luckey, U.; Rössler, A.; Schiefke, I.
Abstract: Background: Non‐adherence to medication is a challenging problem in daily clinical practice. Objective: To assess reasons for non‐adherence in patients with chronic immune‐mediated inflammatory diseases (IMIDs) in a direct comparison including evaluation of treatment necessity and concerns. Methods: ALIGN was a non‐interventional, multicountry, multicentre, self‐administered, cross‐sectional, epidemiologic survey study. Here, we investigate the German, Austrian and Swiss (DACH) cohort. Six hundred thirty‐one patients with different IMIDs (rheumatoid arthritis, ankylosing spondylitis, psoriatic arthritis, plaque psoriasis, Crohn's disease and ulcerative colitis) under systemic therapies were evaluated concerning adherence, beliefs of necessity and concerns towards treatment in patients with IMIDs. Results: The DACH cohort had significantly different levels of adherence depending on the IMID ( P < 0.05) and the type of therapy ( P < 0.05). Based on the significant influence of concerns on treatment adherence ( P < 0.05) and the high belief of treatment necessity, patients could be classified in four attitudinal segments, which were unequally distributed throughout various IMIDs. High concerns had a significant influence on non‐adherence, whereas necessity did not. Older age, female sex, TNFi mono‐, conventional combination and TNFi combination therapy are positively associated with adherence. Conclusions: In the DACH region, patients are less concerned about medication and believe in the necessity of treatment. Therefore, we suggest adapting the communication in the various patient groups.